Discriminating scheelite deposit types using interpretable ensemble learning: A case study from the Xuefengshan Au-Sb-W belt, South China - Xiao-Ran Zhou; Qi-Liang Liu; Biao Liu; Jing-Hua Wu; Safiyanu Muhammad Elatikpo; Fei Deng; Shiwei Cui (Journal of Geochemical Exploration, 2026)

Selective enrichment of fractions in thermal dissolution of high-sulfur coal: Application of solid-phase microextraction technology and construction of ZnO/rGO coatings - Jia-Qi Liu; Xing Fan; Ran-Ran Hou; Xiao-Hui Cao; Binoy K. Saikia; Chao Feng; Jin-Xi Wu; Xiao-Yu Dong (Fuel, 2026)

Heat transfer enhancement and entropy generation analysis of bionic fish-scale structures in narrow rectangular channels for plate-type fuel applications - Xiaoya Liu; Lingke Ran; Xinwen Zhao; Hongguang Xiao; Yongfa Zhang; Ming Ding (Annals of Nuclear Energy, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

An assessment of direct steam sterilization on texture, flavor, and native functional proteins retention in yogurt - Julong Liu; Shusen Li; Ziqiang Li; Ran Xiao; Yong Guo; Erna Sun; Qiruonan Shen; Yuejiao Wang; Tingting Wang; Shuang Du; Wentao Zhang; Chenyuan Wang (Food and Bioproducts Processing, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

Microorganisms immobilized on hydrochar with high specific surface area effectively reduce the incidence rate of pepper phytophthora blight - Mengyang Sun; Yafang Zhou; Huashuai Wang; Xiaozhong Wang; Ran Xiao; Dunyi Liu (Plant and Soil, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

Interfacial engineering of MnO2/Al2O3 catalyst for unique sulfur-promoted benzene oxidation at mild temperatures - Xiao-Ran Liu; Yang Liu; Hao Zhou; Xianliang Yi (Journal of Environmental Management, 2026)

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

Experimental and numerical investigation of flow-induced vibration in CMC turbine blades using fluid-structure interaction - Maojing Ran; Lu Zhang; Zhe Liu; Xingshuang Wu; Tianhang Xiao; Xiguang Gao; Yingdong Song (Engineering Structures, 2026)

Decoding the molecular complexity of coal: A machine learning framework for component classification and solvent selection - Yu-Ying Zhou; Xing Fan; Jin-Xi Wu; Zhen-Yu Gao; Ran-Ran Hou; Chao Feng; Zhong-Qiu Liu; Qing Liu; Xiao-Yu Dong; Peng Liang (Fuel, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Offshore wind power prediction based on improved Hankel-DMD-LSTM hybrid model: Strengthening mode selection and residual compensation mechanism - Tengjiao Guo; Qiang Liu; Xingyu Fang; Mingkun Fang; Yanzhao Wu; Ran Tao; Ruofu Xiao (Ocean Engineering, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Insight into the oxidation mechanism of low-salt Sichuan-style sausages treated with inclusion complexes of tea-polyphenol/β-cyclodextrin/NaCl and electron beam irradiation using machine learning algorithms - Ya Liu; Jiuhong Du; Wenyi Ran; Lihui Huang; Wenyue Yu; Huan Guo; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2026)

A comprehensive review of emerging protein modification methods: modified properties and potential applications - Hao Zhu; Kaifang Guan; Xiaolin Liu; Ran Xiao; Ying Ma; Weihong Lu; Xue Han; Rongchu Wang; Tianjiao Niu (Food Chemistry, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Tailored V/Mn/Ti ratio unlocks high-performance phosphate cathodes for sodium-ion batteries - Zhanhao Zhang; Xingjie Shao; Junjie Fan; Zhiyong Xiong; Yonglin Huo; Lei Ran; Hongcheng Lu; Wanxiu Xiao; Xitao lin; Hongdong Liu; Maowen Xu (Chemical Engineering Journal, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

A chlorinated 2-(2-phenylethyl)chromone in artificial agarwood as a DRD5 agonist and mediates the cAMP/Ca²⁺ signaling pathway to intervene in the growth and proliferation of gastric cancer cells - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Bioinformatics-based discovery of a new norsesquiterpenoid from agarwood targeting CHRM2 and regulating the PI3K-Akt pathway in liver cancer - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Hao-Jie Liang; Yang-Yang Liu (Phytochemistry Letters, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Thermo and LDL-responsive acrylated β-cyclodextrin based microspheres enable targeted oleanolic acid release and LDL removal for atherosclerosis therapy - Yujie Xiao; Xianda Liu; Ziyue Ling; Shifan Chen; Ran Wei; Weifeng Zhao; Changsheng Zhao (Chemical Engineering Journal, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

CoAFNet: a correlation modelling and Attention Fusion Network for semantic change detection - Zhenni Li; Mengying Ran; Jingyi Liu; Shiming Hu; Hanquan Zhang; Dong Xiao (International Journal of Remote Sensing, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Geographical and seasonal dynamics of nutritional and functional profiles in Maiwa yak milk from the Qinghai-Tibetan Plateau - Yanshi Jiang; Rongmei Liu; Xiaolin Liu; Ran Xiao; Weihong Lu; Tianjiao Niu; Ying Ma; Kaifang Guan; Rongchu Wang (International Dairy Journal, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Dolomite reservoir differences in characteristics and controlling factors of grainstone shoal facies in Qixia Formation, Sichuan Basin - Benjian Zhang; Hualing Ma; Xiaojie Huang; Xihua Zhang; Xiao Chen; Fujie Jiang; Chen Xie; Yangui Chen; Ran Liu; Wei Wang; Haitao Sun (Carbonates and Evaporites, 2025)

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

Electrostatic-modulated assembly of charged COF nanosheets into high-performance nanofiltration-based desalination membranes - Shan Luo; Ran Chen; Ruiyuan Zeng; Dai Shi; Youqing Tian; Jiamei Sun; Zifan Song; Yuanhui Xiao; Jiashu Yuan; Jianghuan Shi; Haixiong Liu; Hanyang Liu; et al. (Chemical Engineering Journal, 2025)

Enzymatic and Non-Enzymatic decolorization of synthetic dyes using spent mushroom substrate - Wenjing Xiao; Ya Ran; Xinyu Guo; Yujun Dai; Zhilin Zhang; Jiashu Liu; Changchun Li (World Journal of Microbiology and Biotechnology, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

CdS-mediated electron dynamics in light-assisted anaerobic digestion: Simultaneous cadmium sequestration and methane enrichment by alkali pretreatment - Baowei Zhang; Xiang Tang; Linrui Zhong; Jiangfu Zheng; Huannian Xiao; Yizhan Deng; Zezhong Ran; Mengqi Wei; Lifang Liu; Changzheng Fan (Journal of Hazardous Materials, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

In situ implantable and reactive oxygen species responsive hydrogel loaded with minocycline for functional rehabilitation of traumatic brain injury - Jie Zhou; Yuanyuan Ran; Chenye Qiao; Jingjing Liang; Yufei Wang; Wei Su; Yonghao Xiao; Lin Ye; Jianing Xi; Zongjian Liu (Chemical Engineering Journal, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Trichothecroamides A‒F, antifungal amides from potato associated fungus Trichothecium crotocinigenum - Qiong Chen; Ao-Ran Xu; Bao-Bao Shi; Xiao-Fang Zhang; Ji-Kai Liu; Tao Feng (Phytochemistry, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Impact of ultrasonication on the regeneration of tetracycline-saturated activated carbon and activated coke using persulfate - Xiao Mi; Dongyang Ren; Guobiao He; Yuming Cui; Gangfu Song; Baogui Wang; Yingxu Liu; Yunlong Ran; Tannaz Pak; Guoting Li (Journal of Environmental Chemical Engineering, 2025)

Electrochlorination Fenton-like and Fenton processes for different categories of phosphonates oxidation to orthophosphate: Performance and mechanism characteristics - Sainan Sun; Guanghua Huang; Jiawei Tang; Fazhi Xie; Xiao Wang; Qiang Guo; Hongshuai Kan; Meng Qiao; Yanpeng Liu; Yi Liu; Zixiao Zhu; Xu Zhao; et al. (Journal of Hazardous Materials, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Socioeconomic developments drove regime shifts of agriculture–ecology–economy nexus of social-ecological system: Four-decade lessons from southeast China - Xinhua Li; Chong Jiang; Yixin Wang; Xiaohuang Liu; Jie Liu; Jun Wang; Ying Zhao; Yuexin Xiao; Zhiyuan Yang; Ran Wang (Journal of Environmental Management, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Exploring hydration of air electrodes for protonic ceramic cells: A review - Haosong Di; Zuoqing Liu; Ming Xiao; Yuesheng Bai; Guangming Yang; Zhixin Luo; Wei Wang; Ran Ran; Wei Zhou; Zongping Shao (Chemical Engineering Journal, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Spatial distribution analysis of trailing-edge vortex-shedding flow based on variational mode decomposition - Qiang Liu; Weilong Guang; Zhaoheng Lu; Ran Tao; Di Zhu; Ruofu Xiao (Ocean Engineering, 2024)

Optimized ammonium-nitrate ratios in constructed wetlands for simultaneously efficient nitrogen removal and greenhouse gas reduction - Ling-Min Zhang; Ran Liu; Xiao-Qin Luo; Ying Liu; Xi-Qi Li; Qing-Jie Meng; Hong-Cheng Wang (Journal of Water Process Engineering, 2024)

Selective increase of antibiotic-resistant denitrifiers drives N2O production in ciprofloxacin-contaminated soils - Linfa Fang; Yue Deng; Prakash Lakshmanan; Weibing Liu; Xiufeng Tang; Wenxin Zou; Tong Zhang; Xiaozhong Wang; Ran Xiao; Jinbo Zhang; Xinping Chen; Xiaoxuan Su (Journal of Hazardous Materials, 2024)

A conductive ionogel with Stretchability, low hysteresis and adjustable adhesion for Air/Underwater mechanosensing - Chuanjiang Zhou; Xiao Song; Ran Wei; Shengjie Liu; Zhaoqiang Wu; Hong Chen (Chemical Engineering Journal, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Deciphering the key factors affecting pesticide residue risk in vegetable ecosystem - Daiwei Liu; Tongtong Chen; Yahui Gong; Xuanjing Chen; Wei Zhang; Ran Xiao; Yuheng Yang; Tong Zhang (Environmental Research, 2024)

Customization of indium-based MOFs for enhanced adsorptive and photocatalytic of organic pollutants: Morphology involvement on performance and mechanism - Wenliang Zhang; Yan Wang; Timing Fang; Xiao Tang; Zhezheng Ding; Yunhai Han; Ran Guo; Pengfei Qi; Xiaomin Liu (Chemical Engineering Journal, 2024)

Fibroblast growth factor receptor 4 deficiency in macrophages aggravates experimental colitis by promoting M1-polarization - Luyao Shen; Cong Wang; Ran Ren; Xudong Liu; Dongqin Zhou; Yu Chen; Yu Zhou; Juan Lei; Yang Xiao; Nan Zhang; Huakan Zhao; Yongsheng Li (Inflammation Research, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Moving forward from escaping the poverty trap in China's greenest regions: Examining four decades of socioecological evolution to re-orient sustainable development policies - Xinhua Li; Chong Jiang; Yixin Wang; Jie Liu; Ran Wang; Ying Zhao; Jie Zhang; Haiyan Zhang; Buqing Wang; Yuexin Xiao (Applied Geography, 2024)

Multi-GNSS broadcast ephemeris errors assessment and weight determination of different constellations for SPP - Hang Shen; Ran Li; Shuhui Li; Jingbin Liu; Xiao Chen; Jiajia Xu (Advances in Space Research, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Neuroprotective and vasoprotective effects of herb pair of Zhiqiao-Danggui in ischemic stroke uncovered by LC-MS/MS-based metabolomics approach - Benxing Yao; Di Xu; Qing Wang; Lin Liu; Ziyun Hu; Wenya Liu; Qi Zheng; Huihui Meng; Ran Xiao; Qian Xu; Yudie Hu; Junsong Wang (Metabolic Brain Disease, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Synergistic use of photocatalysis and convergent paired electrolysis for nickel-catalyzed arylation of cyclic alcohols - Zhao-Ran Liu; Xiao-Yu Zhu; Jian-Feng Guo; Cong Ma; Zhiwei Zuo; Tian-Sheng Mei (Science Bulletin, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Coupled effects of human activities and river–Lake interactions evolution alter sources and fate of sedimentary organic carbon in a typical river–Lake system - Shilan Wang; Fengwei Ran; Zhongwu Li; Changrong Yang; Tao Xiao; Yaojun Liu; Xiaodong Nie (Water Research, 2024)

A novel p-type CoSe2 co-catalyst cooperated with hematite for boosting photoelectrochemical water splitting - Shanshan Jiang; Dabo Liu; Dongke Li; Mengyuan Xiao; Yunchou Deng; Yu Han; Ran Tao; Xiaoxing Fan; Kuiyong Liu (Fuel, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Driver–response relationships in a large shallow lake since the Anthropocene: Short‐term abrupt perturbations versus long‐term sustainable pressures - Fengwei Ran; Shilan Wang; Xiaodong Nie; Tao Xiao; Changrong Yang; Yaojun Liu; Zhongwu Li (Global Change Biology, 2024)
Lakes, as integral social‐ecological systems, are hotspots for exploring climatic and anthropogenic impacts, with crucial pathways revealed by continuous sediment records. However, the response of multi‐proxies in large shallow lakes to typical abrupt events and sustained drivers since the Anthropocene remains unclear. Here, we explored the driver‐identification relationships between multi‐proxy peaks and natural and anthropogenic events as well as the attribution of short‐term perturbations and long‐term pressures. To this end, sediment core records, socio‐ecological data, and documented events from official records were integrated into a large shallow lake (Dongting Lake, China). Significant causal cascades and path effects (goodness‐of‐fit: 0.488; total effect: −1.10; p .001) were observed among catchment environmental proxies, lake biogenic proxies, and mixed‐source proxies. The peak‐event identification rate (PEIR) and event‐peak driving rate were proposed, and values of 28.57%–46.43% and 50%–81.25% were obtained, respectively. The incomplete accuracy of depicting event perturbations using sediment proxies was caused by various information filters both inside and outside the lake. PEIRs for compound events were 1.41 (±0.72) and 1.09 (±0.46) times greater than those for anthropogenic‐dominated and natural‐dominated events, respectively. Furthermore, socio‐economic activity, hydrologic dynamics, land‐use changes, and agriculture exerted significant and persistent pressures, cumulatively contributing 55.3%–80.9% to alterations in sediment proxies. Relatively synergistic or antagonistic trends in temporal contributions of these forces were observed after 2000, which were primarily attributed to the “Grain for Green” project and the Three Gorges Dam. This study represents one of the few investigations to distinguish the driver–response relationship of multiple proxies in large shallow lakes under typical event perturbations and long‐term sustained pressures since the Anthropocene. The findings will help policymakers and managers address ecological perturbations triggered by climate change and human activities over long‐term periods.

Different binding properties of odorant-binding protein 8 to insecticides in Orius sauteri - Zhe-Ran Wu; Yi-Wen Pei; Xiao-Qing Zhang; Min Lu; Xiao-Long Liu (Pesticide Biochemistry and Physiology, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Polyethylene microplastics induced inflammation via the miR-21/IRAK4/NF-κB axis resulting to endoplasmic reticulum stress and apoptosis in muscle of carp - Tian-jing Liu; Jie Yang; Jia-wei Wu; Xiao-ran Sun; Xue-jiao Gao (Fish & Shellfish Immunology, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Livestock grazing may weaken N deposition effects on soil C:N:P stoichiometry in alpine grassland of the Qinghai-Tibetan Plateau - Hao Shen; Shikui Dong; Shuai Li; Hanzhong Zheng; Qiyun Wang; Junxiang Liu; Jiannan Xiao; Hui Zuo; Ran Zhang; Xiuchun Yang (CATENA, 2023)

A mesh-free finite-difference scheme for frequency-domain acoustic wave simulation with topography - Xiao-Hui Cai; Chan-Juan Huang; Tao-Ran; Xiao-Ping Fan; Heng Liu (Applied Geophysics, 2023)

Coarse cereals modulating chronic low-grade inflammation: review - Yongzhu Zhang; Esra Capanoglu; Linshu Jiao; Liqing Yin; Xianjin Liu; Ran Wang; Jianbo Xiao; Baiyi Lu (Critical Reviews in Food Science and Nutrition, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Design of a novel chimeric peptide via dual blockade of CD47/SIRPα and PD-1/PD-L1 for cancer immunotherapy - Zheng Hu; Wanqiong Li; Shaomeng Chen; Danhong Chen; Ran Xu; Danlu Zheng; Xin Yang; Shuzhen Li; Xiuman Zhou; Xiaoshuang Niu; Youmei Xiao; Zhuoying He; et al. (Science China Life Sciences, 2023)

Correction to: dual role of endoplasmic reticulum stress-ATF-6 activation in autophagy and apoptosis induced by cyclic stretch in myoblast - Qiang Zhang; Guirong Liu; Ran Liu; Jun Liu; Xuemin Zeng; Dapeng Ren; Xiao Yan; Xiao Yuan (Apoptosis, 2023)

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

A versatile organic silicate aluminum hybrid coagulant for broad-spectrum removal of heavy metal ions - Jin-Wei Liu; Tao Fu; Guang-Dong Sun; Xiao-Ran Shen; Sheng Liu; Yang He; Yi Xu; Hua-Zhang Zhao (Chemical Engineering Journal, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dynamic mode structure analysis of the near-wake region of a Savonius-type hydrokinetic turbine - Yanzhao Wu; Weilong Guang; Ran Tao; Jie Liu; Ruofu Xiao (Ocean Engineering, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

A significant loop of lake sedimentation state links catchment eco‐surroundings and lake biogenic regime shifts - Fengwei Ran; Xiaodong Nie; Shilan Wang; Tao Xiao; Changrong Yang; Yi Liu; Lingxia Wang; Yaojun Liu; Xin Chu; Zhongwu Li (Limnology and Oceanography, 2023)
As an important destination for upstream materials and element accumulation, lake sediments hold a multitude of contextual information about climatic changes and anthropogenic disturbances. However, understanding the lake sedimentation state to link catchment pressures and biogenic regime shifts remains challenging. To address this, research was conducted on the lake sedimentation state, including the dynamics, catchment drivers, effects on biogenic regimes, and responses to typical historical events using nine sediment cores from Dongting Lake, China, a typical global priority ecoregion. Three transitions of lake sedimentation state were distinguished over the century (1937, 1968, and 1993), whereby hydrologic dynamics and land‐use changes in the watershed were the direct drivers with relative contributions of 16.30% and 14.56%, respectively. Lake sedimentation state and organic matter inputs not only preceded sediment biogenic elements at the shift time but also exhibited nonlinear trigger effects on biogenic element contents ( R 2 = 0.47, p

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Observed Taylor cap around a seamount intensified by a surface mesoscale eddy in the Northwest Pacific - Yansong Liu; Qiang Ren; Fei Yu; Jianfeng Wang; Ran Wang; Feng Nan; Yanan Ding; Tongtong Zheng; Chuanzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Climate Dynamics, 2023)

Nitrate_dependent suberization regulates cadmium uptake and accumulation in maize - Anle Chen; Tong Liu; Yan Deng; Ran Xiao; Tong Zhang; Yuan Wang; Yuheng Yang; Prakash Lakshmanan; Xiaojun Shi; Fusuo Zhang; Xinping Chen (Science of The Total Environment, 2023)

Impacts of EDTA on the fate of nutrients and heavy metals during the hydrothermal carbonization of poultry manure - Xuhao Chen; Xiaoxia Fan; Kunpeng Gao; Yang Cheng; Ke Zhang; Liyuan Liu; Lingfa Fang; Jong-Hwan Park; Xinping Chen; Ran Xiao (Journal of Environmental Chemical Engineering, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

Dual role of endoplasmic reticulum stress-ATF-6 activation in autophagy and apoptosis induced by cyclic stretch in myoblast - Qiang Zhang; Guirong Liu; Ran Liu; Jun Liu; Xuemin Zeng; Dapeng Ren; Xiao Yan; Xiao Yuan (Apoptosis, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

Anthropogenic activities control the source dynamics of sediment organic carbon in the lower reach of an inland river - Changrong Yang; Zhongwu Li; Shilan Wang; Fengwei Ran; Xiaodong Nie; Yaojun Liu; Tao Xiao (Water Research, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Qiang Ren; Yansong Liu; Ran Wang; Feng Nan; Jianfeng Wang; Xinyuan Diao; Zifei Chen; Fei Yu; Chuangzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans; however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy–Kuroshio interactions based on large-scale in situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018–2019 (12 deployed east of Taiwan within a 3 × grid) were used to reveal the three-dimensional structure of mesoscale eddies and their interaction with Kuroshio. The results show a strengthening (weakening) of the tilt of the pycnocline, which has also caused a deeper (shallower) pycnocline in eastern Taiwan following an anticyclonic (cyclonic) interaction with Kuroshio, which resulted in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downward (upward) movement at the center of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for further research on energy exchange during eddy–Kuroshio interactions.

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Recent advancements in antibiotics containing wastewater treatment by integrated bio-electrochemical-constructed wetland systems (BES-CWs) - Shuang Luo; Zhi-Yuan Zhao; Ying Liu; Ran Liu; Wen-Zong Liu; Xiao-Chi Feng; Ai-Jie Wang; Hong-Cheng Wang (Chemical Engineering Journal, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

The pre-addition of “blocking” proteins decreases subsequent cellulase adsorption to lignin and enhances cellulose hydrolysis - Jingyun Liu; Jie Wu; Yi Lu; Huaiyu Zhang; Qi Hua; Ran Bi; Orlando Rojas; Scott Renneckar; Senqing Fan; Zeyi Xiao; Jack Saddler (Bioresource Technology, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Intensive stretch-activated CRT-PMCA1 feedback loop promoted apoptosis of myoblasts through Ca2+ overloading - Dapeng Ren; Ran liu; Xiao Yan; Qiang Zhang; Xuemin Zeng; Xiao Yuan (Apoptosis, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Effects of combined soil amendments on Cd accumulation, translocation and food safety in rice: a field study in southern China - Lei Shi; Zhaohui Guo; Shuaixia Liu; Xiyuan Xiao; Chi Peng; Wenli Feng; Hongzhen Ran; Peng Zeng (Environmental Geochemistry and Health, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Interleukin-17A Contributed to the Damage of Blood-CNS Barriers During Streptococcus suis Meningitis - Lei Xu; Xi Lu; Peng Xiao; Ran Liu; Kunlong Xia; Meizhou Wu; Meilin Jin; Anding Zhang (Molecular Neurobiology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Elabela prevents angiotensin II-induced apoptosis and inflammation in rat aortic adventitial fibroblasts via the activation of FGF21–ACE2 signaling - Juan-Juan Song; Mei Yang; Ying Liu; Jia-Wei Song; Xiao-Yan Liu; Ran Miao; Zhen-Zhou Zhang; Yu Liu; Yi-Fan Fan; Qian Zhang; Ying Dong; Xin-Chun Yang; et al. (Journal of Molecular Histology, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Geochemistry and sedimentology of the Upper Ordovician–lower Silurian black shale in the northern margin of the Upper Yangtze Platform, South China: implications for depositional controls on organic-matter accumulation - B. Xiao; S. G. Liu; B. Ran; Z. W. Li (Australian Journal of Earth Sciences, 2020)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Early Hemolysis Within Human Intracerebral Hematomas: an MRI Study - Ran Liu; Haijiao Li; Ya Hua; Richard F. Keep; Jiangxi Xiao; Guohua Xi; Yining Huang (Translational Stroke Research, 2019)

Structure–activity relationship investigation of coumarin–chalcone hybrids with diverse side-chains as acetylcholinesterase and butyrylcholinesterase inhibitors - Lu Kang; Xiao-Hui Gao; Hao-Ran Liu; Xue Men; Hong-Nian Wu; Pei-Wu Cui; Eric Oldfield; Jian-Ye Yan (Molecular Diversity, 2018)

Discovery of potent and selective acetylcholinesterase (AChE) inhibitors: acacetin 7- O -methyl ether Mannich base derivatives synthesised from easy access natural product naringin - Hao-ran Liu; Xue Men; Xiao-hui Gao; Lin-bo Liu; Hao-qun Fan; Xin-hua Xia; Qiu-an Wang (Natural Product Research, 2018)

Monazite behaviour during isothermal decompression in pelitic granulites: a case study from Dinggye, Tibetan Himalaya - Jia-Min Wang; Fu-Yuan Wu; Daniela Rubatto; Shi-Ran Liu; Jin-Jiang Zhang; Xiao-Chi Liu; Lei Yang (Contributions to Mineralogy and Petrology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

The ferredoxin-dependent glutamate synthase (OsFd-GOGAT) participates in leaf senescence and the nitrogen remobilization in rice - Dong-Dong Zeng; Ran Qin; Mei Li; Md. Alamin; Xiao-Li Jin; Yu Liu; Chun-Hai Shi (Molecular Genetics and Genomics, 2017)

Isolation of a new cytotoxic polyhydroxysterol from the South China Sea soft coral Sinularia sp. - Huan Sun; Fen Liu; Mei-Ran Feng; Qi Peng; Xiao-Jian Liao; Ting-Ting Liu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)

A new sesquiterpene from the gorgonian coral Menella sp. - Qi Peng; Fen Liu; Huan Sun; Xiao-Jian Liao; Mei-Ran Feng; Ting-Ting Liu; Zheng-Xiong Xu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

Procalcitonin levels in patients with positive blood culture, positive body fluid culture, sepsis, and severe sepsis: a cross-sectional study - Ying Yu; Xia-Xi Li; Ling-Xiao Jiang; Meng Du; Zhan-Guo Liu; Zhong-Ran Cen; Hua Wang; Zhen-Hui Guo; Ping Chang (Infectious Diseases, 2016)

Fragment virtual screening based on Bayesian categorization for discovering novel VEGFR-2 scaffolds - Yanmin Zhang; Yu Jiao; Xiao Xiong; Haichun Liu; Ting Ran; Jinxing Xu; Shuai Lu; Anyang Xu; Jing Pan; Xin Qiao; Zhihao Shi; Tao Lu; et al. (Molecular Diversity, 2015)

Sam68 Promotes NF-κB Activation and Apoptosis Signaling in Articular Chondrocytes during Osteoarthritis - Libin Xu; Chi Sun; Sihui Zhang; Xinbao Xu; Leilei Zhai; Youhua Wang; Shitao Wang; Zhongbing Liu; Hongbing Cheng; Min Xiao; Ran Tao; Dongmei Zhang (Inflammation Research, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Paradevosia shaoguanensis gen. nov., sp. nov., Isolated from a Coking Wastewater - Shuang Geng; Xin-Chi Pan; Ran Mei; Ya-Nan Wang; Ji-Quan Sun; Xue-Ying Liu; Yue-Qin Tang; Xiao-Lei Wu (Current Microbiology, 2015)

Nitratireductor shengliensis sp. nov., Isolated from an Oil-Polluted Saline Soil - Xin-Chi Pan; Shuang Geng; Ran Mei; Ya-Nan Wang; Hua Cai; Xue-Ying Liu; Yue-Qin Tang; Yong Nie; Si-Yuan Ye; Xiao-Lei Wu (Current Microbiology, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Ottowia shaoguanensis sp. nov., Isolated From Coking Wastewater - Shuang Geng; Xin-Chi Pan; Ran Mei; Ya-Nan Wang; Ji-Quan Sun; Xue-Ying Liu; Yue-Qin Tang; Xiao-Lei Wu (Current Microbiology, 2014)

An efficient multistep ligand-based virtual screening approach for GPR40 agonists - Sihui Yao; Tao Lu; Zifan Zhou; Haichun Liu; Haoliang Yuan; Ting Ran; Shuai Lu; Yanmin Zhang; Zhipeng Ke; Jinxing Xu; Xiao Xiong; Yadong Chen (Molecular Diversity, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Growth rate, catalase and superoxide dismutase activities in rock carp (Procypris rabaudi Tchang) exposed to supersaturated total dissolved gas - Xiao-qing Liu; Ke-feng Li; Jun Du; Jia Li; Ran Li (Journal of Zhejiang University-SCIENCE B, 2011)

Three new fatty acids from the roots of Boehmeria nivea (L.) Gaudich and their antifungal activities - Qiong-Ming Xu; Yan-Li Liu; Xiao-Ran Li; Xia Li; Shi-Lin Yang (Natural Product Research, 2011)

Effects of the Metals Lead and Zinc on the Growth, Development, and Reproduction of Pardosa Astrigera (Araneae: Lycosidae) - Xiao-qiong Chen; Zheng-tian Zhang; Ran Liu; Xiu-Ling Zhang; Jian Chen; Yu Peng (Bulletin of Environmental Contamination and Toxicology, 2011)

Genomic characterization of a proventriculitis-associated infectious bronchitis coronavirus - Chao-ting Xiao; Ran Liu; Zhu-yuan Song; Min Liao; Ji-yong Zhou (Virus Genes, 2010)

Studies on the anti-psoriasis constituents of Oplopanax elatus Nakai - De-Qiang Dou; Xiao-Yan Hu; Yue-Ran Zhao; Ting-Guo Kang; Feng-Yun Liu; Hai-Xue Kuang; David C. Smith (Natural Product Research, 2009)

Iron contributes to the formation of catechol isoquinolines and oxidative toxicity induced by overdose dopamine in dopaminergic SH-SY5Y cells - Ran Wang; Hong Qing; Xiao-Qian Liu; Xiao-Lin Zheng; Yu-Lin Deng (Neuroscience Bulletin, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

Effect of different dietary raw to pre-gelatinized starch ratios on growth performance, feed utilization and body composition of juvenile yellowfin seabream (Sparus latus) - Xiao-Yi Wu; Yong-Jian Liu; Li-Xia Tian; Kang-Sen Mai; Ran Guo; Sheng-Jie Jin (Aquaculture International, 2007)

Effects of aromatizable and nonaromatizable androgens on the sex inversion of red-spotted grouper (Epinephelus akaara) - Guang-Li Li; Xiao-Chun Liu; Hao-Ran Lin (Fish Physiology and Biochemistry, 2006)